2022
DOI: 10.48550/arxiv.2201.03887
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Post maximum light and late time optical imaging polarimetry of type I superluminous supernova 2020znr

F. Poidevin,
C. M. B. Omand,
I. Pérez-Fournon
et al.

Abstract: Optical imaging polarimetry was conducted on the hydrogen poor superluminous supernova SN2020znr during 3 phases after maximum light (≈ +34 days, +288 days and +289 days). After instrumental and interstellar polarization correction, all measurements are consistent with null-polarization detection. Modelling the light curve with a magnetar spin-down model shows that SN2020znr has similar magnetar and ejecta parameters to other SLSNe. A comparison of the best-fit values discussed in the literature on SN2017egm a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…Both studies concluded that the inner ejecta were more aspherical than the outer ejecta. However, several other SLSNe have had detections consistent with zero polarization and thus have a spherical ejecta (e.g Leloudas et al 2015;Cikota et al 2018;Lee 2019Lee , 2020Poidevin et al 2022), implying that significant asymmetries may only appear in a minority of SLSNe. Vurm & Metzger (2021) relaxed the assumption that a magnetar's power output is 100% thermalized by the SLSN ejecta.…”
Section: Breakdown Of Assumptionsmentioning
confidence: 99%
“…Both studies concluded that the inner ejecta were more aspherical than the outer ejecta. However, several other SLSNe have had detections consistent with zero polarization and thus have a spherical ejecta (e.g Leloudas et al 2015;Cikota et al 2018;Lee 2019Lee , 2020Poidevin et al 2022), implying that significant asymmetries may only appear in a minority of SLSNe. Vurm & Metzger (2021) relaxed the assumption that a magnetar's power output is 100% thermalized by the SLSN ejecta.…”
Section: Breakdown Of Assumptionsmentioning
confidence: 99%